PARAMETRLI KÓRSETKISHLI TEŃLEMELER HÁM TEŃSIZLIKLERDI SHESHIW USILLARI - Djumabaev, N.; Kuanıshbaev, T. (SCIENCE and SOCIETY, 2022)
The article presents various methods of parametric exponential equations and the inequality.